2012
DOI: 10.1093/carcin/bgs380
|View full text |Cite
|
Sign up to set email alerts
|

Replication of GWAS-identified neuroblastoma risk loci strengthens the role of BARD1 and affirms the cumulative effect of genetic variations on disease susceptibility

Abstract: Several neuroblastoma (NB) susceptibility loci have been identified within LINC00340, BARD1, LMO1, DUSP12, HSD17B12, DDX4, IL31RA, HACE1 and LIN28B by genome-wide association (GWA) studies including European American individuals. To validate and comprehensively evaluate the impact of the identified NB variants on disease risk and phenotype, we analyzed 16 single nucleotide polymorphisms (SNPs) in an Italian population (370 cases and 809 controls). We assessed their regulatory activity on gene expression in lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
127
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(134 citation statements)
references
References 20 publications
7
127
0
Order By: Relevance
“…This study indicated that three SNPs in the FLJ22536 gene mapping to chromosome 6p22 were significantly associated with neuroblastoma susceptibility [8]. The association of 6p22 locus with neuroblastoma susceptibility has been replicated in subsequent studies using diverse populations, including African-Americans [13] and Italians [14].…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…This study indicated that three SNPs in the FLJ22536 gene mapping to chromosome 6p22 were significantly associated with neuroblastoma susceptibility [8]. The association of 6p22 locus with neuroblastoma susceptibility has been replicated in subsequent studies using diverse populations, including African-Americans [13] and Italians [14].…”
Section: Introductionmentioning
confidence: 63%
“…Latorre et al [13] investigated the association of all these three polymorphisms in 390 African-American neuroblastoma patients and 2500 healthy controls; however, they failed to prove the association with altered neuroblastoma susceptibility for any of three SNPs. Capasso et al [14] attempted to test the association between two polymorphisms (rs6939340 A>G and rs4712653 T>C) and neuroblastoma susceptibility with 370 cases and 809 controls in an Italian population; they confirmed a significant association between both of these two polymorphisms and neuroblastoma susceptibility. As far as we knew, no validation study was performed among Asians except ours; we found that all of these three SNPs were associated with decreased neuroblastoma susceptibility in the current study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Familial neuroblastoma is rare (approximately 1%), and most of these cases harbour germline mutations in ALK 1. In contrast, the genetic bases of sporadic neuroblastoma remain largely unknown 2, 3. Through a genomewide association study (GWAS) of sporadic neuroblastoma, we have reported common single nucleotide polymorphisms (SNPs) associated with neuroblastoma susceptibility at CASC15 4, BARD1 5, LMO1 6, DUSP12 7, HSD17B12 7, DDX4/IL31RA 7, HACE1 8 and LIN28B 8 loci.…”
Section: Introductionmentioning
confidence: 99%